Current mismatch repair deficiency tumor testing practices and capabilities: A survey of Australian pathology providers. (7th October 2018) - Mascarenhas, Lyon; Shanley, Susan; Mitchell, Gillian; Spurdle, Amanda B.; Macrae, Finlay; Pachter, Nicholas; Buchanan, Daniel D.; Ward, Robyn L.; Fox, Stephen; Duxbury, Elaine; Driessen, Rebecca; Boussioutas, Alex
Abstract: Aim & Methods: An electronic survey of the Royal College of Pathologists of Australasia accredited pathology services was conducted to assess Lynch syndrome tumor screening practices and to identify barriers and capabilities to screen newly diagnosed colorectal and endometrial tumors in Australia. Results: Australia lacks a national policy for universal mismatch repair‐deficient (dMMR) testing of incident colorectal and endometrial tumors cases. Routine Lynch syndrome tumor screening program for colorectal and/or endometrial tumors was applied by 95% (37/39) of laboratories. Tumor dMMR screening methods varied; MMR protein immunohistochemistry (IHC) alone was undertaken by 77% of 39 laboratories, 18% performed both IHC and microsatellite instability testing, 5% did not have the capacity to perform in‐house testing. For colorectal tumors, 47% (17/36) reported following a universal approach without age limit, 30% (11/36) tested only "red flag" cases; 6% (3/36) on clinician request only. For endometrial tumors, 37% (12/33) reported clinician request generated testing, 27% (9/33) were screening only "red flag" cases, and 12% (4/33) carried out universal screening without an age criteria. BRAF V600E mutation testing of colorectal tumors demonstrating aberrant MLH1 protein expression by IHC was the most common secondary tumor test, with 53% of laboratories performing the test; 15% of laboratories also applied the BRAF V600E test to endometrial tumors with aberrant MLH1 expression despite no evidence for its utility. Tumor testing for MLH1 promoter methylation was performed by less than 15% laboratories. Conclusion: Although use of tumor screening for evidence of dMMR is widely available, protocols for its use in Australia vary widely. This national survey provides a snapshot of the current availability and practice of tumor dMMR screening and identifies the need for a uniform national testing policy.